Incorporation of rubber-steel bearing isolation in multi-storey muilding - Islam, A. B. M. Saiful; Jumaat, Mohd Zamin; Hussain, Raja; Alam, Md Ashraful (Journal of Civil Engineering and Management, 2014)
Base isolation incorporation has moved towards a popular technology in the seismic vulnerable regions. The system mitigates lateral action of tremor hazard providing flexibility of structures. Implementing base isolation on buildings in the soil and seismic condition of medium risk seismicity is currently an important issue. A thorough investigation is of burning need for buildings to be incorporated with base isolator and to carry out dynamic analysis. The study provides incorporation of rubber-steel bearings and focuses on the structural changes. Designs of base isolation bearings are performed along with structural viability check. Lead rubber bearing (LRB) and high damping rubber bearing (HDRB) have been inserted on the corresponding structural bases. In finite-element approach, link element simulates the bearing. Bi-linear hysteretic behaviour is presented for LRB and equivalent linear model simulated HDRB. Linear static, free vibration and dynamic frequency-domain analyses are performed for both isolated and non-isolated buildings under bidirectional site-specific earthquake. The study reveals that for multi-storey buildings, isolation can drastically reduce seismic responses. Furthermore, flexibility of buildings predicts some structural savings for reduced responses. Good agreement has been achieved through rapid solution in frequency-domain approach. In medium risk earthquake-prone area, rubber-steel bearing isolators can be beneficially inserted.